Spacecraft Flight in the Atmosphere - Virgili Llop, Josep (Cranfield University, 2014)
Spacecraft that orbit in Low Earth Orbit travel through a tenuous atmosphere and hence experience aerodynamic forces that can become quite significant, specially at low altitudes. The presence of these forces can become a major design driver for missions that fly at very low altitudes. Unfortunately, spacecraft aerodynamics are not well understood. In this dissertation, a CubeSat mission is proposed which will study rarefied-gas aerodynamics, with the objective of determining the effect of surface composition, surface finishing and flow incidence angle on the drag and lift coefficients with an error of less than 5% using a novel method. The CubeSat, has been named ΔDsat, because this study, will be performed using differential measurements of drag and lift coefficients in order to eliminate any measurement bias. ΔDsat carries 4 deployable fins that can rotate independently and expose different surface types to the flow at different incident angles. In addition, in the dissertation four methods to exploit the aerodynamic forces for the missions advantage are proposed and described in detail. The first one is aerostability, which by shaping the spacecraft appropriately, the resulting aerodynamic torques stabilise the attitude spacecraft with respect to the flow. The second method uses aerodynamic drag and lift to change de inclination of a decaying spacecraft in order to maintain the Sun-synchronous aspect of an orbit whilst decaying. The required lift to drag ratio is in the order of 1.0-1.6, which is not currently achievable (it is theoretically possible), but it could be achieved if drag compensating propulsion is used (thus becoming a fuel saving strategy). The third method controls the atmospheric re¬entry interface (the location of the burn-up) by modulating the drag, hence controlling the decay profile. When applied to ΔDsat an error of less than 200 km 3cr on the re-entry location is achieved. Finally, aerostable spacecraft can be used to perform in-situ measurements of the atmospheric winds, by observing their attitude evolution. The aerostable ΔDsat CubeSat would be capable of determining the cross-track winds with an error of less 4 m/s 3cr.